The Effect of Knowledge Sharing and Digital Competence on Innovative Work Behavior with Thriving at Work as an Intervening Variable Among Echelon II Officials in West Nusa Tenggara Provincial Government - Zahrul Martayadi; Thatok Asmony; Siti Nurmayanti (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study investigates the effect of knowledge sharing and digital competence on innovative work behavior, with thriving at work as an intervening variable, among Echelon II Officials of the West Nusa Tenggara Provincial Government, Indonesia. A quantitative causal research design was employed using census sampling covering all 41 Heads of Regional Apparatus Organizations, with data collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with bootstrapping procedures, drawing on theoretical frameworks from Jong & Den Hartog, Matzler et al., Ferrari's DigComp 2.2, and Spreitzer & Porath. Of seven hypotheses examined, five were supported: knowledge sharing did not directly influence innovative work behavior but significantly predicted thriving at work, which fully mediated the knowledge sharing–innovative work behavior relationship, while digital competence directly and positively influenced both innovative work behavior and thriving at work, though thriving at work did not mediate the digital competence innovative work behavior path. These findings suggest that digital competence serves as a direct driver of public sector innovation, whereas knowledge sharing operates through employees' psychological well-being, implying that the NTB Provincial Government should prioritize strategic digital leadership programs and cultivate reflective knowledge-sharing cultures, with future research encouraged to adopt longitudinal designs and examine additional mediators such as organizational climate and leadership style.